Lo sviluppo psicologico del bambino e dell’adolescente. Sanità e malattia - Fagioli, Francesca (Il sogno della farfalla, 2006)
This article analyzes the identity and development of the child and adolescent, taking its lead from a critique of the myth of Oedipus and the principle underlying it whereby human identity is constructed through identifications. Such a principle can be overturned by simply considering that at birth not only do we have the setting in motion of the biological organism but also a psychological activity and reality that allow the baby a healthy relationship with the mother. On this basis, the baby can develop his own identity in a harmonious fusion between body and psychic reality; consequently, at adolescence he will be in the position to live through the anatomic-physiological revolution of his body without running up against pathologies.